PEMBERIAN HAK GUNA USAHA (HGU) DI IBU KOTA NUSANTARA (IKN) DALAM PERSPEKTIF UNDANG UNDANG POKOK AGRARIA (UUPA) DAN PEMBANGUNAN EKONOMI NASIONAL - Farhan Gibran, Muhammad; Sumarja, FX; Adhan, Sepriyadi (Penerbit Lafadz Jaya, 2025)
The granting of Land Cultivation Rights (HGU) for up to 190 years in the Nusantara Capital City (IKN), as stipulated in Government Regulation No. 12 of 2023, raises fundamental legal and economic concerns. This policy is considered to deviate from the fundamental principles of the Basic Agrarian Law (UUPA), particularly regarding the social function of land, state control, and equitable access to agrarian resources. This study applies a normative juridical method with statutory, conceptual, and historical approaches, supported by qualitative-prescriptive analysis. It examines key legal frameworks including the UUPA, the IKN Law, the Investment Law, and their implementing regulations. The analysis is guided by the Theory of Justice (John Rawls), Economic Analysis of Law (Richard Posner), legal certainty, and statutory hierarchy principles. Findings reveal that the long-term HGU scheme risks undermining legal certainty, promoting land monopolization by private investors, and marginalizing local communities. Economically, the absence of periodic evaluation mechanisms may lead to inefficient land use and hinder inclusive, sustainable development. The study concludes that the HGU policy in IKN requires regulatory revision to ensure alignment with agrarian justice, legal predictability, and long-term national economic goals.